A DEIXIS ANALYSIS OF SONG LYRICS IN NIKI’S “NICOLE” ALBUM - Rohaili, Alya; Syaputri, Komala Dwi (Universitas Muhammadiyah Metro, 2024)
This study aimed to identify the kinds of Deixis and their influence on the formation of meaning in song lyrics. The object of the study was the entirety of the songs under Niki's album, namely, the